Effect of traditional Chinese medicine formula Guilu Xian on in vitro fertilization and embryo transfer outcome in older women with low prognosis: study protocol for a prospective, multicenter, randomized double-blind study - Yingjie Ma; Xianling Cao; Jingyan Song; Dandan Gao; Xinlei Wang; Li Li; Zhengao Sun (figshare, 2021)
Abstract Introduction In recent years, the prevalence of infertility has significantly increased and has become a global reproductive health problem. The female ovarian reserves have been shown to decrease progressively with an increase in age. Besides, the rate of embryo implantation and clinical pregnancy also decreases. Traditional Chinese medicine has been widely applied in assisted reproductive technology. It is reported to have a significant influence on improving the quality of oocytes, improving endometrial receptivity, increasing clinical pregnancy rate, reducing pregnancy-related complications, etc. Therefore, this study will investigate the effect of Guilu Xian, a traditional Chinese medicine formula on IVF-ET outcome in older women with low prognosis. Methods and analysis This trial is a prospective, multicenter, randomized double-blind clinical trial. A total of 120 infertile patients with low prognosis and receiving IVF or ICSI in 3 public hospitals in China will be randomly divided into two parallel groups: Guilu Xian group (n = 60) and placebo group (n = 60). Patients in both groups will be treated with antagonist regimens to promote ovulation, and all the patients will be required to take the medication from the 2nd to 4th day of the menstrual cycle to the day of egg retrieval. A comparison of the total number of oocytes obtained, the fertilization rate, clinical pregnancy rate, embryo quality, embryo implantation rate, and early spontaneous abortion rate between the experimental group and the placebo group will be performed. Trial registration Chinese Clinical Trials Registry ChiCTR1900028255 . Registered on 16 December 2019.
Keywords: Medicine; Cell Biology; Physiology; Pharmacology; Biotechnology; Immunology; Mathematical Sciences not elsewhere classified; Developmental Biology; Cancer; Science Policy; Mental Health